Reflectance, illumination, and appearance in color constancy - McCann, John J.; Parraman, Carinna; Rizzi, Alessandro (Frontiers in Psychology, 2014)
We studied color constancy using a pair of identical 3-D Color Mondrian displays. We viewed one 3-D Mondrian in nearly uniform illumination, and the other in directional, nonuniform illumination. We used the three dimensional structures to modulate the light falling on the painted surfaces. The 3-D structures in the displays were a matching set of wooden blocks. Across Mondrian displays, each corresponding facet had the same paint on its surface. We used only 6 chromatic, and 5 achromatic paints applied to 104 block facets. The 3-D blocks add shadows and multiple reflections not found in flat Mondrians. Both 3-D Mondrians were viewed simultaneously, side-by-side. We used two techniques to measure correlation of appearance with surface reflectance. First, observers made magnitude estimates of changes in the appearances of identical reflectances. Second, an author painted a watercolor of the 3-D Mondrians. The watercolor's reflectances quantified the changes in appearances. While constancy generalizations about illumination and reflectance hold for flat Mondrians, they do not for 3-D Mondrians. A constant paint does not exhibit perfect color constancy, but rather shows significant shifts in lightness, hue and chroma in response to the structure in the nonuniform illumination. Color appearance depends on the spatial information in both the illumination and the reflectances of objects. The spatial information of the quanta catch from the array of retinal receptors generates sensations that have variable correlation with surface reflectance. Models of appearance in humans need to calculate the departures from perfect constancy measured here. This article provides a dataset of measurements of color appearances for computational models of sensation.